Legal Regulations Regarding Online Donation Management Through Platforms - Dhevi Nayasari; M. Yanto; Muhammad Za'im Muhibbulloh; Ardita Melvi (Universitas Islam Lamongan, 2025)
The development of digital technology has driven changes in various aspects of life, including in fundraising activities or online donations which are now widely carried out through various digital platforms, but this convenience also poses challenges in legal protection, transparency and accountability of donation management. Along with technological advances, fundraising activities can now be done via the internet. In this online donation process, donations given by donors are not directly received by the beneficiaries, this opens up opportunities for Platform organizers and Campaigners to commit acts of misuse of funds. Therefore, this study will discuss how the legal regulations regarding the management of online donations through platforms and how legal sanctions are imposed on platforms for embezzlement of online donation funds in Indonesia from the perspective of civil law, criminal law and government supervision of online fundraising activities. This study uses a normative legal method, is descriptive analysis, with a statutory approach. The results of the study show that; online donation management is regulated in general regulations, the legal materials used are primary legal materials including: Law Number 9 of 1961 concerning the collection of money or goods, Law Number 11 of 2008 concerning transactions and electronics, Law Number 15 of 2002, Law Number 27 of 2022, Government Regulation Number 29 of 1980 and Regulation of the Minister of Social Affairs Number 28 of 2021. These regulations have not fully regulated specifically regarding online donations. Meanwhile, legal sanctions for misuse of funds from online donations through platforms include civil and administrative criminal sanctions in accordance with Article 372 of the Criminal Code and Article 1365 of the Civil Code.